2017
DOI: 10.1111/nph.14668
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometeorology organizes intra‐annual patterns of tree growth across time, space and species in a montane watershed

Abstract: Tree radial growth is often systematically limited by water availability, as is evident in tree ring records. However, the physiological nature of observed tree growth limitation is often uncertain outside of the laboratory. To further explore the physiology of water limitation, we observed intra-annual growth rates of four conifer species using point dendrometers and microcores, and coupled these data to observations of water potential, soil moisture, and vapor pressure deficit over 2 yr in the Northern Rocky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Comparative studies conducted on several conifer species from the northern hemisphere have demonstrated that the ending of xylogenesis phases is generally more dispersed compared to their onset, as complex interactions between temperature constraints and water limitations may occur (Rossi et al, ). Tree dimension had very little effect on the timing of wood formation and xylem differentiation, suggesting a predominant climatic control over stem growth in forest ecosystems subject to water limitation (Martin, Looker, Hoylman, Jencso, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies conducted on several conifer species from the northern hemisphere have demonstrated that the ending of xylogenesis phases is generally more dispersed compared to their onset, as complex interactions between temperature constraints and water limitations may occur (Rossi et al, ). Tree dimension had very little effect on the timing of wood formation and xylem differentiation, suggesting a predominant climatic control over stem growth in forest ecosystems subject to water limitation (Martin, Looker, Hoylman, Jencso, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al () proposed that the degree of organization of vegetation along hydrologic flow paths effectively represents the dependency of local ecosystems to lateral redistribution of soil moisture. While we acknowledge that lateral redistribution of moisture likely plays a substantial role in organizing vegetation along topographic gradients, topographically organized transfers of water vapor and energy (i.e., vapor pressure gradients) also significantly impact spatial patterns of atmospheric demands for moisture and therefore, ecosystem productivity (Martin et al, ; Oberhuber et al, ). Furthermore, soil processes (such as weathering and transport) and properties (such as texture, depth, and composition) often align along topographic gradients (McAuliffe, ; Pachepsky et al, ; Rasmussen et al, ) and contribute to the organization of soil moisture and plant available nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it will be important for ecological studies to explicitly identify and incorporate the spatial distribution of active hillslope hydrology processes, and their potential to change with climate shifts, if we are to fully predict ecosystem trajectories in water‐limited landscapes (Fan et al, ; Simeone et al, ; Tai et al, ). One potential way forward is to perform site‐specific analysis across the ecosystem sensitivity gradient (Figures d and a) using field‐based hydrology approaches (e.g., Martin et al, ; Hawthorne & Miniat, ; Hoylman et al, ) or distributed ecohydrology modeling frameworks that couple the water and carbon cycles (e.g., Maneta & Silverman, ; Simeone et al, ; Tague & Band, )…”
Section: Limitations and Implicationsmentioning
confidence: 99%